Biogenic Gold Nanoparticles as Potent Antibacterial and Antibiofilm Nano-Antibiotics against Pseudomonas aeruginosa - Syed Ghazanfar Ali; Mohammad Azam Ansari; Mohammad A. Alzohairy; Mohammad N. Alomary; Sami AlYahya; Mohammad Jalal; Haris M. Khan; Sarah Mousa Maadi Asiri; Wasim Ahmad; Abbas Ali Mahdi; Ahmed M. El-Sherbeeny; Mohammed A. El-Meligy (MDPI AG, 2020)
Abstract: Plant-based synthesis of eco-friendly nanoparticles has widespread applications in many fields, including medicine. Biofilm—a shield for pathogenic microorganisms—once formed, is difficult to destroy with antibiotics, making the pathogen resistant. Here, we synthesized gold nanoparticles (AuNPs) using the stem of an Ayurvedic medicinal plant, Tinospora cordifolia, and studied the action of AuNPs against Pseudomonas aeruginosa PAO1 biofilm. The synthesized AuNPs were characterized by techniques such as ultraviolet-visible spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, energy-dispersive X-ray diffraction, X-ray diffraction, scanning electron microscopy (SEM), and transmission electron microscopy. The AuNPs were spherically shaped with an average size of 16.1 nm. Further, the subminimum inhibitory concentrations (MICs) of AuNPs (50, 100, and 150 µg/mL) greatly affected the biofilm-forming ability of P. aeruginosa, as observed by crystal violet assay and SEM, which showed a decrease in the number of biofilm-forming cells with increasing AuNP concentration. This was further justified by confocal laser scanning microscopy (CLSM), which showed irregularities in the structure of the biofilm at the sub-MIC of AuNPs. Further, the interaction of AuNPs with PAO1 at the highest sub-MIC (150 µg/mL) showed the internalization of the nanoparticles, probably affecting the tendency of PAO1 to colonize on the surface of the nanoparticles. This study suggests that green-synthesized AuNPs can be used as effective nano-antibiotics against biofilm-related infections caused by P. aeruginosa.